Aspects of Payout Policy of German Savings Banks - Volker Kleff; Martin Weber (Kredit und Kapital, 2010)
Aspects of Payout Policy of German Savings Banks The German savings banks' distribution of profits among their public owners (i. e. municipalities and districts) requires that legal criteria are met ensuring the banks' adequate funding via retained profits. In line with the legal framework, our analysis of savings banks in four federal states confirms that profitability and portfolio risk are important determinants of the savings banks' payout decision. Heavily indebted municipalities and districts, however, might have a strong interest in the savings banks' payouts to mitigate their financial distress. In fact, we find that the payout decision is also influenced by the public owners' interest. (G21) – – Aspekte der Ausschüttungspolitik deutscher Sparkassen Die Ausschüttungen der deutschen Sparkassen an ihre Gewährträger (Städte und Kreise) werden streng gesetzlich reguliert, um eine angemessene Refinanzierung der Sparkassen über einbehaltene Gewinne zu gewährleisten. Unsere Untersuchung der deutschen Sparkassen in vier Bundesländern bestätigt, dass entsprechend den gesetzlichen Vorgaben die Profitabilität und das Portfoliorisiko der Sparkassen wichtige Bestimmungsgrößen der Ausschüttungsentscheidung sind. Stark verschuldete Gewährträger könnten darüber hinaus ein großes Interesse an den Ausschüttungen haben, um ihre Finanzsituation zu verbessern. Tatsächlich finden wir heraus, dass die Ausschüttungsentscheidung auch von den Interessen der Gewährträger beeinflusst wird.
Keywords: 330